Intracranial artery disease in the general population - Johnsen, Liv-Hege (UiT The Arctic University of Norway, 2024)
Intracranial aneurysms (IAs) and intracranial artery stenoses (ICAS) are vascular conditions of the brain that can lead to stroke. An IA is an outpouching of the artery wall that can rupture, causing an aneurysmal subarachnoid hemorrhage (aSAH), a severe form of stroke with high mortality and potential for disability. ICAS involves narrowing of brain arteries, commonly due to atherosclerosis, which can result in ischemic strokes due to reduced blood flow. Data on the prevalence of both unruptured IAs (UIAs) and ICAS in Western populations are scarce, with definitions varying across studies. These definitions differ regarding UIA size thresholds, the extent of stenosis, and inclusion of extradural lesions. Prevalence data on intradural UIAs, along with aSAH incidence, are necessary to assess the risk of aneurysm rupture. While ICAS is a significant cause of strokes in Asians and African Americans, its importance in Western populations has been less emphasized. The lack of prevalence data on UIA and ICAS in the Western population was the main motivation for this study. This MRI study, as a part of the Tromsø Study, used 3D time-of-flight 3 Tesla MR angiography to identify UIAs and ICAS in 1878 adults aged 40-84 years. With sequences like 3D T2-fluid attenuated inversion recovery (FLAIR), 3D T1-weighted, and susceptibility-weighted images (SWI) we assessed cortical infarcts, lacunes, white matter hyperintensities, and brain parenchymal fraction (BPF) as a proxy for brain atrophy. We found a UIA prevalence of 6.6% for UIAs ≥2 mm, varying dependent on definition criteria. Alongside aSAH incidence data, we calculated annual rupture risks for UIAs, 0.03% for <5 mm and 1.6% for ≥5 mm UIAs, supporting prophylactic treatment for the latter. ICAS prevalence (≥50%) was 6.0%. We found an independent association between ICAS and traditional cardiovascular risk factors as well as cortical infarctions, thalamic lacunes, periventricular white matter hyperintensities, and brain atrophy. Intrakranielle aneurismer og stenoser ...